Comments concerning crack width calculation in joints of steel-concrete composite slabs - Michał Knauff; Marcin Niedośpiał (Budownictwo i Architektura, 2014)
In this paper some aspects of the calculation of the width of cracks in joints of steel-concrete composite slabs are reported. The code concerning design of composite steel and concrete structures for the calculation of crack widths refers to the code of reinforced concrete structures. The application of the formula, which takes into account „tension stiffening”, seems to lead to surprising results - for the elements with small reinforcement ratio, the obtained stress is much greater than the stress calculated in classical way i.e. without tension stiffening. The authors present the derivation of this formula - the result corresponds to the formula in the code but in the paper an additional case is taken into account. Furthermore, the authors suggest to consider two types of areas as in the RC code. Type D (D from "discontinuity") should be analyzed in the close surrounding of the column and type B (B from Bernoulli) areas at some distance from the column.